More on 666

666 = 1^{6} - 2^{6} + 3^{6}

666 = 6 +6 +6 +6^{3}+ 6^{3}+6^{3}

666 = 2^{2}+  3^{2}+ 5^{2}+ 7^{2}+ 11^{2}+ 13^{2}+ 17^{2}

\phi(666) = 666
where
\phi(n) = \text{number of integers less than n and co-prime with n }

Advertisements

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s